An unusual case of mouth opening limitation caused by bilateral coronoid process hyperplasia: A case report - F Sarkarat; R Kahali (Islamic Azad University, 2018)
Coronoid process hyperplasia is the enlargement of the coronoid processes and may lead to their impingement upon the zygomatic arch and limitation of the mouth opening. It can be unilateral or bilateral and usually affects men in the second decade of life. The etiology of the coronoid process hyperplasia is unknown. The aim of treatment is to restore the mouth opening and the only available treatment is surgery. Intraoral coronoidectomy has been suggested as the treatment of choice. Although the immediate increase in jaw mobility is gained after surgery, proper post-operative rehabilitation and physical therapy is necessary to maintain the mouth opening.